1995
DOI: 10.1152/ajpcell.1995.269.5.c1235
|View full text |Cite
|
Sign up to set email alerts
|

Ion channel classes in purified olfactory cilia membranes: planar lipid bilayer studies

Abstract: Ciliary membrane fragment fusion to planar lipid bilayers resulted in the insertion of four ion channel types. cAMP-activated, cation-selective channels could be detected only in the absence of Ca2+ and had a conductance of 23 pS. They exhibited an apparent dissociation constant (Kd) for the cyclic nucleotide of approximately 30 microM and an estimated permeability ratio (PNa/PK) of 2.4. The cAMP cation-selective channel coinserted with a K(+)-selective channel refractory to cAMP, Ca2+, and D-myo-inositol 1,4,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

1995
1995
2005
2005

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 23 publications
4
13
0
Order By: Relevance
“…This may have been one of the first demonstrations of TRP vanilloid receptor-type functional channels in cilia. Cyclic AMP activated the 23-pS cation channels in vertebrate olfactory cilia (24) and modulated a high conductance K ϩ channel, displaying several open substates with conductances of 34, 80, and 130 pS (24), which is highly reminiscent of PC2 function (21). The presence of cAMP-activated 8 pS chloride channels has also been determined by steady-state noise analysis of ligand-induced currents (36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may have been one of the first demonstrations of TRP vanilloid receptor-type functional channels in cilia. Cyclic AMP activated the 23-pS cation channels in vertebrate olfactory cilia (24) and modulated a high conductance K ϩ channel, displaying several open substates with conductances of 34, 80, and 130 pS (24), which is highly reminiscent of PC2 function (21). The presence of cAMP-activated 8 pS chloride channels has also been determined by steady-state noise analysis of ligand-induced currents (36).…”
Section: Discussionmentioning
confidence: 99%
“…1d). Primary cilia from confluent LLC-PK1 cells were isolated with a technique adapted from previous reports (24,25). Briefly, confluent LLC-PK1 cells were deciliated by a quick exposure to a high Ca 2ϩ solution and concentrated in a sucrose density gradient.…”
Section: Identification and Isolation Of Primary Cilia From Llc-pk1 Cmentioning
confidence: 99%
“…In addition, this odorant-triggered inhibitory conductance is sensitive to charybdotoxin (CTX), a toxin that blocks Ca 2+ -activated K+ channels [11]. In support of this notion, a CTX-sensitive Ca 2+ -activated K+ conductance has been recently reported to be present in toad olfactory cilia [12].…”
Section: Introductionmentioning
confidence: 89%
“…Later, a planar lipid bilayer study of a toad olfactory ciliary membrane fraction suggested the presence of a 240 pS conductance BK Ca channel (in symmetrical 200 mM KCl). Its K 0.5 for Ca 2+ was 46 μM and it was blockable by 42 nM ChTx [20]. This channel was presumably derived from the cilia, although the purity of the membrane fraction was not assessed.…”
Section: Discussionmentioning
confidence: 99%